Noise Exposure Causes Hearing Loss In Workers In The Agricultural Industry Area - Maharani, Ceria Dwi Karla; Nisa, Indika Khoirun; Kurniyawan, Enggal Hadi; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad; Afandi, Alfid Tri (International Health Sciences Journal, 2025)
Noise exposure can hurt the health of industrial workers, especially the hearing loss in agricultural industry workers. This study aims to analyze noise exposure that can cause hearing loss in agricultural workers. The method used is a literature review approach to 10 journals published nationally and internationally that are reputable with search engines through 3 databases: Google Scholar, Semantic Scholar, and Pubmed in the 2019-2024 publication period. This study found that several factors can cause hearing loss in agricultural industry workers, consisting of two factors that cause disorders: individual and worker factors. Individual factors are age and level of knowledge, while work factors are length of service, length of work, noise intensity, and use of Personal Protective Equipment (PPE). Workers need to increase their knowledge regarding the importance of using Personal Protective Equipment (PPE) to reduce the risk of hearing loss in the agricultural industry. Therefore, health workers, especially nurses, must be involved in educating agricultural industry workers.